Cross‐domain bearing fault diagnosis with refined composite multiscale fuzzy entropy and the self organizing fuzzy classifier. Issue 3 (3rd November 2020) - Gituku, Esther W.; Kimotho, James K.; Njiri, Jackson G.
Abstract: In this article, the use of refined composite multiscale fuzzy entropy (RCMFE) for cross‐domain diagnosis of bearings is introduced and verified with two publicly available datasets of varying operating conditions, a factor that challenges the diagnostic ability of trained models. For classification, the self organizing fuzzy (SOF) classifier is used. The diagnostic framework which primarily only involves extracting RCMFE feature and training the SOF classifier, is able to detect and isolate faults with over 97% accuracy when the classes are comprised of a single fault type and size. Compared to related works, the proposed approach does not require deep learning for feature extraction nor any domain adaptation technique as the RCMFE feature is robust against changing operating conditions. Furthermore, the method does not need target domain data during training. With regard to fault isolation, when the classes in the training data contain all the available fault sizes instead of a single size, the classifier can distinguish inner race faults from outer race and ball fault with an average accuracy of 96%. However, the accuracy for differentiating ball and outer race faults falls slightly to an average of 86%. Thus even for the latter arrangement which poses a tougher transfer learning problem, the proposed approach still performs very well. Abstract : The use of refined composite multiscale fuzzy entropy (RCMFE) for cross‐domain diagnosis of bearings is here introduced and verified with two publicly available datasets. Compared to related works, the proposed approach does not require deep learning for feature extraction nor any domain adaptation technique as the RCMFE feature is robust against changing operating conditions. Furthermore, the method does not need target domain data during training.